Adaptation and validation of the Diabetes Management Self-Efficacy Scale to Brazilian Portuguese - Ana Emilia Pace; Lilian Cristiane Gomes; Daniela Comelis Bertolin; Helena Maria Almeira Macedo Loureiro; Jaap Van Der Bijl; Lillie M. Shortridge-Baggett
Objective: to perform the cultural adaptation and validation of the Diabetes Management Self-efficacy Scale for Patients with Type 2 Diabetes Mellitus with a Brazilian population sample. Method: cross-sectional methodological study in which the adaptation and validation process included the stages recommended in the literature. Construct validity and reliability were assessed with 200 adults with type 2 diabetes mellitus. Results: the items indicated by the panel of judges and by the target population were adjusted in the cultural adaptation to improve clarity and understanding. The instrument's four factors remained in the confirmatory factor analysis with factor loadings of items greater than 0.30, except for factor 4; convergent validity, verified by the multitrait-multimethod analysis, presented inter-item correlations from 0.37 to 0.92, while for discriminant validity, 100% of the items presented greater correlation in their own factors. Cronbach's coefficient alpha for the total scale was 0.78, ranging from 0.57 to 0.86 among factors. Conclusion: semantic, cultural, conceptual and idiomatic equivalences were achieved and the instrument's Brazilian version also presented psychometric properties that showed evidence of reliability and validity. Thus, it can be applied both in clinical practice and research. Self-efficacy is useful for planning and assessing educational interventions, as well as predicting behavior modification in self-care.